Effiency at high work rates in world class skiers - Ettema, G.; Sandbakk, O.; Leirdal, S.; Holmberg, H. C. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Energy delivery and mechanical efficiency, a measure related to technique, are key factors in endurance performance. Efficiency is normally measured at low intensities to obtain steady state aerobic conditions. However, in competitive skiing, efficiency is important at higher intensities with a combination of aerobic and anaerobic energy delivery. Therefore, the present study aimed to study efficiency at relatively high, and up to maximal, work rates. Furthermore, we aimed to investigate the effects of performance level by comparing World Class and National level athletes. Methods: Eight world class (26.1±3.5 yr, 184.8±5.6 cm, 83.3±6.4 kg, fat percent 8.8±2.6%, FIS-points 20.5±13.1) and eight national class (24.5±2.3 yr, 186.4±6.6cm, 82.8±6.6 kg, fat percent 9.9±1.5%, FIS-points 87.4±27.7) Norwegian male cross country skiers participated in the study. After a preliminary warm up, all athletes performed three 5- min stages at 14, 16 and 18 km h-1 on a 5% inclination using the skating V-2 technique while roller skiing on a treadmill. Furthermore, the athletes performed an incremental treadmill velocity test at a 5% incline, leading to a maximal obtainable speed after 5-7min. Gross efficiency was calculated by external power output divided by internal power. External power was calculated taking into account both work rate against gravity and frictional rolling forces. Internal power was calculated using gas exchange and blood lactate values. The effect of velocity on efficiency and group differences with regard to this was tested using a one-way ANOVA for repeated measures. Furthermore, the groups were compared for efficiency at their own maximal speed during the incremental test. Results: Compared at absolute work rates (i.e., the 3 velocities) the world class skiers showed higher efficiencies than the national class (15.17±0.37%; 15.15±0.43%; 15.21±0.63% vs 13.95±0.71%; 14.43±0.58%; 14.54±0.57%, at 14, 16 and 18 km h-1, respectively). The group differences were highly significant (P=0.002). The statistical analysis showed that the velocity effect was not significant (P=0.073). The apparent small trend was caused by the difference between 14 and 16 km h-1 in the national class group. Compared at relative work rates (maximal speed during the incremental test) the 2 groups seemed to have a similar difference in efficiency, as at absolute work rates, but it did not reach statistical significance (15.58±1.04% vs. 14.78±0.62%; P=0.083). Discussion: The current results indicate that, in addition to the higher energy delivery capacity, world class athletes also utilise a more effective technique at an absolute work rate (i.e., velocity) than national level athletes. However, at the same relative work rate, these differences, at least statistically, are less clear.